Analysis and reflections on the national security and defense policy (2001-2018) in pursuit of strengthening national security - Zavaleta Ramos, Humberto (2020)
The objective of this research was to analyze the situation of institutionality of the National Defense System at the political and strategic level during the period 2001-2018, and to define its impact on the formulation of the National Security and Defense Public Policy. The research was of theoretical-descriptive type and qualitative approach; the design was non-experimental and the method used was hermeneutic. The population was made up of documents on public policies, and the sample was taken from documents related to national security and defense policies found in the facilities of the Ministry of Defense. The information gathering technique was documentary analysis, the instrument used being a list of documents to be searched and the route of virtual or real sites. It was found that, during the period of study, the State elaborated and formulated up to three national security and defense policies; however, these were not viable, since they were not implemented or articulated in the three levels of government, this as a consequence of a series of unwise decisions in the higher level of Peru's national security and defense. Thus, it was concluded that from 2001 to 2018 there was a period of time characterized by institutional weakness at the higher level of Peru's security and national defense, a situation that did not allow for the design, articulation and implementation of an adequate national security and defense policy.